Curriculum Renewal and Alignment Expedited - JACQUELINE KRESS (Academic Chairpersons Conference Proceedings, 2016)
Keeping program curricula current, aligned, effective, and engaging can be daunting. This session provides experience extracting and clarifying implied learning objectives, content, and other program elements and using them in an expedited curriculum renewal and alignment process successful with diverse programs such as business, engineering, graphic arts, and teacher education.
Keywords: Curriculum development; program evaluation; curriculum alignment; quality improvement; curriculum leadership